Potencialidades da língua crioula na educação ambiental: escolas do ensino secundário no Município da Praia, Cabo Verde. - Pereira, Nízia Olimpia Dias Borges (2013)
The understanding the cultural identity of the Cape Verdeans should be the first step for a project of environmental education that make use of the full linguistic capabilities of their country and of its specificities. The use of the mother tongue, Creole which ancestrally linked to the identity of the people of Cape Verde displays a potential proportional to the own identity, conservationist by the nature. Despite being the main vehicle of communication of Cape Verdeans,residents and those in the diaspora, the Creole language has failed to achieve the status of Cape Verde official language since the country political independence, 38 years ago. With a strong presence in culture of the Islands, the Creole, however, stands out only in informal environments, whereas Portuguese is established as official language of the country. The Creole has been literally away from the Administration and from the formal and informal education processes. Concerning the Environmental Education, the discrimination of Creole reaches levels of sheer absence. This research seeks to search and to understand the potential of the use of Cape Verde mother tongue, the Creole, as an instrument for the Environmental Education at the secondary schools level in the Municipality of Praia, proven through interviews targeting teachers, coordinators and directors of secondary schools in the territory of Municipality of Praia. The research clearly points out to valorize Creole, inserting it as language of support, sideways with the Portuguese language with regard to Environmental Education, lacking political will of decision-makers for its deployment. The findings shows that Capeverdean mother tongue is acknowledged to have great potential, as an instrument of behaviors changes trough out environmental degradation and its impact on society, in particular for generations to come.